Analisa Kegagalan Sambungan Las Pada Tiang Penyangga Dermaga - Syahputra, Koko Nusyi; Nugroho, Aris Widyo (Semesta Teknika, 2015)
Welded join failure analysis of broken jetty head strut has been carried out to find out the root cause of the failure which was obverved at the ring welding. Specimens being made of unbroken and broken struts were characterized and analyzed. The results show that the chemical composition of the based metal and the strut welded joins especially their phosporus content were close to that of the ASTM A 252 grade 2 standard. A common phenomenon was noted on the hardness testing result where the hardness numbers of the weld metal zone were found being higher than those of the base metal. The Widmanstatens stucture was noticed on both the weld metal and the coarse grain zone. Further examination of the macrostructures revealed that blow holes and incomplete fusions were detected on the weld metal of the broken struts. These flaws may the root cause of the failure because they acted as an initial crack that may propagate until fracture.